2017
DOI: 10.1371/journal.pone.0188668
|View full text |Cite
|
Sign up to set email alerts
|

Children and young people’s perceptions of energy drinks: A qualitative study

Abstract: BackgroundConsumption of soft drinks is declining in many countries, yet energy drink sales continue to increase, particularly amongst young consumers. Little is currently known about the drivers behind these trends. Energy drinks are high in sugar and caffeine, and evidence indicates that regular or heavy use by under 18s is likely to be detrimental to health. This study aimed to explore children and young people’s attitudes and perceptions in relation to energy drinks in a UK context.MethodsEight focus group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(61 citation statements)
references
References 39 publications
5
53
1
2
Order By: Relevance
“…Recent Canadian research showed that Red Bull Energy Drink is one of the top five most frequently advertised food and beverage products on children’s and teens’ favorite websites [12]. Further, qualitative research in the UK found that respondents aged 10–14 identified a wide variety of media through which they were targeted with CED promotional messages, including the internet, TV, computer games, bus stop advertisements, supermarket promotions, and sponsorship of sports or other events [13]. Indeed, CEDs are still commonly marketed to and consumed by young people and used within contexts that are advised against, such as during sports and with alcohol [11,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Recent Canadian research showed that Red Bull Energy Drink is one of the top five most frequently advertised food and beverage products on children’s and teens’ favorite websites [12]. Further, qualitative research in the UK found that respondents aged 10–14 identified a wide variety of media through which they were targeted with CED promotional messages, including the internet, TV, computer games, bus stop advertisements, supermarket promotions, and sponsorship of sports or other events [13]. Indeed, CEDs are still commonly marketed to and consumed by young people and used within contexts that are advised against, such as during sports and with alcohol [11,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…La mayor parte de los estudios sobre consumo de "bebidas energéticas" se han sido realizado en niños o adolescentes en edades comprendidas entre 12-18 años 11 . En los últimos años se han realizado pocos estudios en universitarios, y los realizados en estudiantes de Medicina valoran aspectos diferentes del consumo y no son comparables entre sí 7,8,[12][13][14] .…”
Section: Discussionunclassified
“…En cuanto a la motivación o justificación del consumo, mientras en adolescentes preuniversitarios se relaciona más su consumo con actividades sociales, deportivas o uso de videojuegos 11,21 , nuestros alumnos señalan como primera justificación "mantenerse despierto para estudiar" y por "su sabor". Este dato coindice con la mayor parte de estudios realizados en estudiantes de Medicina, en los que la justificación del consumo era para mantenerse más activo y despierto para estudiar 8 y porque les gustaba el sabor de este tipo de bebidas 16 .…”
Section: Discussionunclassified
“…Qualitative research can, at times, be overlooked in relation to its capacity to enact meaningful change; however, given the multidimensional nature of 'health problems', the integration of multidisciplinary approaches is of great value [47]. The rich, in-depth understandings often generated through qualitative research of specific 'health problems', and the contexts in which they occur, can provide powerful evidence to inform and instigate policy-level interventions and legislative change [48]. In order to bring about change that is meaningful for rural populations, we must reflect upon, and make explicit in our analysis and reporting of qualitative research, the characteristics of the rural environments in which we locate our inquiry into diagnostic, treatment and follow-up pathways and cancer experiences of people living in rural settings.…”
Section: A New Research Agendamentioning
confidence: 99%